Synthesis and characterization of epoxy composites filled with Pb, Bi or W compound for shielding of diagnostic x-rays - Noor Azman, N.; Siddiqui, Salim; Low, I. (2013)
Lead chloride, bismuth oxide and tungsten oxide filled epoxy composites with different weight fractions were fabricated to investigate their x-ray transmission characteristics in the x-ray diagnostic imaging energy range (40–127 kV) by using a conventional laboratory x-ray machine. Characterizations of the microstructure properties of the synthesized composites were performed using synchrotron radiation diffraction, backscattered electron imaging microscopy, three-point bend test and Rockwell hardness test. As expected, the x-ray transmission was decreased by the increment of the filler loading. Meanwhile, the flexural modulus and hardness of the composites were increased through an increase in filler loading. However, the flexural strength showed a marked decrease with the increment of filler loading (≥30 wt%). Some agglomerations were observed for the composites having ≥50 wt% of filler.